A descriptive study of antithrombotic medication patterns in adult patients with recent venous thromboembolism - Allahwerdy F; Pan S; Feehan M; Jones AE; Munger MA; Witt DM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Objectives: The objective of this study is to describe the most common self-reported antithrombotic therapy utilization patterns in a national cohort of patients with recent venous thromboembolism (VTE). Methods: Extant data from a national online survey administered to 907 patients 18 years of age or older with VTE in the last two years were analyzed. Patients' self-reported antithrombotic usage patterns used during three phases of treatment for the most recent VTE episode were summarized using descriptive statistics. Results: The following overall antithrombotic usage patterns were identified: warfarin (38.7%), direct oral anticoagulants (DOACs) (26.1%), switching between warfarin and DOACs (13.3%), aspirin only (8.7%), switching between different DOACs (4.5%), injectable anticoagulants only (3.9%), and no treatment (4.7%). Extended antithrombotic therapy beyond 90 days was reported by 65.7% of patients. Aspirin coadministration with anticoagulant therapy occurred for 33.7%. Conclusions: In this national sample of recent VTE sufferers warfarin therapy remains the most used anticoagulant followed closely by DOAC therapy. Switching between warfarin and DOACs and between different DOACs was common which could indicate adverse events or affordability issues. Aspirin coadministration with anticoagulant therapy was present in 1 of 3 patients and is a potential medication safety intervention for anticoagulation providers.